1999
DOI: 10.1002/1529-0131(199907)42:7<1370::aid-anr10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol allows reduction of naproxen dose among patients with naproxen-responsive osteoarthritis pain: A randomized, double-blind, placebo-controlled study

Abstract: Objective. To demonstrate that in patients receiving naproxen for the pain of osteoarthritis (OA), the addition of tramadol will allow a reduction in the naproxen dosage without compromising pain relief.Methods. This trial consisted of a 5-week openlabel run-in and an 8-week double-blind phase. Patients with at least moderate pain (>40 mm on a 100-mm visual analog scale) of OA of the knee after a 1-week medication washout were treated with naproxen 500 mg/day for 1 week. Patients whose pain scores were reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 15 publications
1
28
0
5
Order By: Relevance
“…A total of 22 publications were retrieved for more detailed evaluation [2,5,6,7,8,9,10,11,12,15,18,19,20,22,23,24,27,29,31,32,34,36,40]. Three were excluded because of double publication [36] or lack of data for our analysis (.…”
Section: Included Trialsmentioning
confidence: 99%
“…A total of 22 publications were retrieved for more detailed evaluation [2,5,6,7,8,9,10,11,12,15,18,19,20,22,23,24,27,29,31,32,34,36,40]. Three were excluded because of double publication [36] or lack of data for our analysis (.…”
Section: Included Trialsmentioning
confidence: 99%
“…39 In osteoarthritis, a randomized controlled study on 236 patients (mean age 60 years) showed that the addition of an opioid allowed for a reduction in NSAIDs without compromising pain relief. 40 This can be of bene®t in the mainstay of chronic pain management, since NSAIDs are known to be associated with cardiac and renal toxicities, a particular problem for the elderly population.…”
Section: A Place For Opioids In Low Back Pain?mentioning
confidence: 99%
“…), Steroids (glucocorticoid) and DMARDs (methotrexate, Cyclosporin A) for managing moderate to severe cases of arthritic pain, stiffness and inflammation (Quan et al, 2008), the side effects of these drugs are often deleterious, which includes gastrointestinal irritation, cardio vascular problem, drug dependency etc. (Schnitzer et al, 1999). All these drawbacks of available medications have revived the interest in our ancestral conventional approach of food therapy, herein the focus being therapy with molluscan extract against arthritis.…”
Section: Introductionmentioning
confidence: 99%